PERBEDAAN LITERASI EMERGEN ANAK TAMAN KANAK-KANAK DI DAERAH PERKOTAAN DAN PINGGIRAN - Astuti, Tri Puji (Jurnal Psikologi, 2014)
AbstractThe aim of this study is to describe the development of emergent literacy in kindergarten children and to compare the development of emergent literacy of kindergarten children in the urban and sub urban area of Semarang city. In order to collect data, the Emergent Literacy developmental Test was used (part of the test was adapted from the Get Ready To Read by Whitehurst). In total, 36 children aged 4-5 years participated in the study. The results showed that kindergarten children from urban area scored higher significantly (13.188 Â± 3.43) in the emergent literacy than children from sub urban area (10.00 Â± 3.146; t(35) = 2.903; p = 0.003).